The Wouldbegoods: Being the Further Adventures of the Treasure Seekers - Nesbit, E. (Edith), 1858-1924 (Salt Lake City, UT : Project Gutenberg, 1997)
"The Wouldbegoods: Being the Further Adventures of the Treasure Seekers" by E. Nesbit is a novel published in 1901. After causing chaos at home in Blackheath, the Bastable children are sent to the countryside for summer. There, alongside the Foulkes siblings, they earnestly attempt to perform good deeds. But their noble intentions consistently backfire, leading to unexpected mishaps and unintended consequences. Narrated by young Oswald Bastable himself, the story captures childhood schemes told from a child's perspective. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/The_Wouldbegoods
Release date is 1997-01-01
Produced by Jo Churcher, and David Widger
Keywords: Adventure stories; Siblings -- Juvenile fiction; England -- Juvenile fiction; Country life -- Juvenile fiction; Children -- Juvenile fiction; Families -- Juvenile fiction